Incidence of Non-alcoholic Fatty Liver Disease among Referral Outpatients to the Internal Medicine Clinic - Farnaz, Barzi (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: Non-alcoholic fatty liver disease (NAFLD) is as silent comorbidity in many different settings including; diabetes mellitus (DM), obesity, and hyperlipidemia. In this study, we aimed to determine the incidence of NAFLD in referral outpatients to the internal medicine clinic to evaluate correlations between NAFLD in the other clinical backgrounds. Materials and Methods: We performed a cross-sectional study on 88 consecutive referral patients to the internal medicine clinic. Patients with a history of liver disease and alcohol consumption were excluded. Liver ultrasound was performed for diagnosing of NAFLD to be mild to moderate (Grade 1), or moderate to a severe degree of involvement (Grade 2). Clinical backgrounds of the patients, including history and laboratory exam tests such as age, exercise, and DM as well as lipid profile, and liver enzyme test results investigated in our study. Results: The incidence of NAFLD was 62% (40% Grade 2; 60% Grade 1). Patients with NAFLD had a higher body mass index, (30 ± 5 vs. 27 ± 4; P = 0.04). They were younger than patients who had not NAFLD (46 ± 15 vs. 58 ± 10 years; P = 0.0001). Total cholesterol level was higher in patients with NAFLD (198 ± 46 vs. 175 ± 46 mg/Dl; P = 0.03). Patients with NAFLD had higher serum alanine aminotransferase (ALT) level (50 ± 14 vs. 46 ± 15 IU/l; P = 0.0001). The aspartate aminotransferase/ALT ratio was lower in patients with NAFLD (0.8 ± 0.3 vs. 1 ± 0.2; P = 0.0001). Patients with NAFLD had sedentary lifestyle compared to those with normal liver (P = 0.001). Conclusion: More than half of the referral outpatients to the internal medicine clinic have NAFLD. It occurs in the young age population of patients and has a strong correlation with high-cholesterol level and sedentary lifestyle.